Sex differences in operating room care giver perceptions of patient safety: a pilot study from the Veterans Health Administration Medical Team Training Program. Issue 2 (8th February 2010) - Carney, B T; Mills, P D; Bagian, J P; Weeks, W B
Abstract : Background: Achieving a culture of safety is believed to be an important mechanism for improving patient safety. The Safety Attitudes Questionnaire (SAQ) measures provider perceptions of patient safety culture across six domains; higher scores denote more positive perceptions. Although professional differences on the SAQ have been explored, sex differences have not. Methods: The SAQ was administered to operating room (OR) care givers at nine Department of Veterans Affairs hospitals. We determined the mean domain scores by care giver profession and sex, used analysis of variance to compare mean scores across professions, used t tests to compare mean scores between sexes and created regression models of the six patient safety domains. Results: The SAQ was completed by 187 OR care givers. Older care givers were significantly more likely to report favourable perceptions of teamwork climate; surgeons were significantly more likely to report favourable perceptions of working conditions; anaesthesia providers were significantly more likely to report favourable perceptions of stress recognition but also less favourable perceptions of safety climate. Women were significantly more likely to report less favourable perceptions of job satisfaction and working conditions. Conclusion: This pilot study confirms previously reported profession differences in OR care giver patient safety attitudes. We also found previously unreported sex differences. Educational efforts designed to enhance patient safety should be designed so that they address such differences.